2022
DOI: 10.1186/s12891-022-05230-y
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-loaded calcium sulfate beads in spinal surgery for patients with spondylodiscitis: a clinical retrospective study

Abstract: Background Various surgical techniques for treating spondylodiscitis have been proposed, but the optimal surgical treatment remains controversial. In this study, we propose a new procedure that is implanting antibiotic-loaded calcium sulfate (CS) beads into the disc after debridement using the Quadrant channel combined with percutaneous fixation through a single-stage posterolateral approach for the treatment of spondylodiscitis. Thus, the purpose of this study is to assess the safety and effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… [22] also described the use of a PMMA strut graft as the LDDS in treatment of patients with spinal osteomyelitis. Gentamicin, tobramycin, vancomycin, and clindamycin are the most widely used in ABC [20 , 57] . Gentamicin and tobramycin covers for gram negative bacteria whereas vancomycin and clindamycin covers for gram positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… [22] also described the use of a PMMA strut graft as the LDDS in treatment of patients with spinal osteomyelitis. Gentamicin, tobramycin, vancomycin, and clindamycin are the most widely used in ABC [20 , 57] . Gentamicin and tobramycin covers for gram negative bacteria whereas vancomycin and clindamycin covers for gram positive bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al. [20] used a mixture of ABC with 0.5 g of vancomycin hydrochloride with cefoperazone and sulbactam sodium for both gram positive and gram-negative coverage respectively. In their study, antibiotic loaded calcium sulfate beads were described to be safe in managing spondylodiscitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated this technique to be effective in treating spinal surgical site infections. 15,16…”
Section: Established Clinical Uses Of Antibiotic Cement In Orthopaedi...mentioning
confidence: 99%